Associations between late and moderately preterm birth and smoking, alcohol, drug use and diet: a population-based case–cohort study. Issue 6 (13th May 2015) - Smith, Lucy K; Draper, Elizabeth S; Evans, T Alun; Field, David J; Johnson, Samantha J; Manktelow, Bradley N; Seaton, Sarah E; Marlow, Neil; Petrou, Stavros; Boyle, Elaine M
Abstract : Objective: This study explores the associations between lifestyle factors and late and moderate preterm birth (LMPT: 32 +0 –36 +6 weeks' gestation), a relatively under-researched group. Study design: A population-based case–cohort study was undertaken involving 922 LMPT and 965 term (37+ weeks' gestation) singleton live and stillbirths born between 1 September 2009 and 31 December 2010 to women residing in Leicestershire and Nottinghamshire, UK. Poisson multivariable regression models were fitted to estimate relative risks (RR) of LMPT birth associated with maternal smoking, alcohol and recreational drug use, and diet. Results: Women who smoked during pregnancy were at 38% increased risk of LMPT birth compared with non-smokers (RR 1.38, 95% CI (1.04 to 1.84)). Low consumption of fruit and vegetables was associated with a 31% increased risk compared with those who reported eating higher consumption levels (RR 1.31 (1.03 to 1.66)). Women who did not have any aspects of a Mediterranean diet were nearly twice as likely to deliver LMPT compared with those whose diet included more Mediterranean characteristics (RR 1.81 (1.04 to 3.14)). Women who smoked and consumed low levels of fruit and vegetables (5% of women) were at particularly high risk (RR=1.81 (1.29 to 2.55)). There was no significant effect of alcohol or recreational drug use on LMPT birth. Conclusions: Smoking and poor diet during pregnancy, factors that strongly impact on very preterm birth, are also important at later gestations and experienced together are associated with an elevated rate of risk. Our findings suggest early cessation of smoking during pregnancy may be an effective strategy to reduce LMPT births.